The effect of porosity of a biphasic ceramic scaffold on human skeletal stem cell growth and differentiation in vivo. Issue 12 (9th April 2013) - Aarvold, Alexander; Smith, James O.; Tayton, Edward R.; Lanham, Stuart A.; Chaudhuri, Julian B.; Turner, Irene G.; Oreffo, Richard O. C.
<x xml:space="preserve">Abstract</x> Skeletal stem cell (SSC) growth on a novel porous HA/TCP scaffold has been investigated in vivo. The effect of porosity on osteogenic differentiation was assessed by comparing two groups of scaffolds with differing porosity but controlled pore size. Histology, microCT, scanning electron microscopy, and biochemical analysis were used to assess SSC proliferation and differentiation. The 45 pores per inch (ppi) scaffold demonstrated a greater increase in density than the 30 ppi scaffold following in vivo culture, and a reduction in dimensions of the pores and channels of the higher porosity scaffold was observed, indicating generation of new tissue within the pores. All scaffolds supported SSC proliferation but the higher scaffold porosity augmented osteogenic differentiation. ALP specific activity was enhanced on the 45 ppi scaffold compared to the 30 ppi scaffold. These studies demonstrate the importance of porosity in scaffold design and impact therein for tissue engineering application. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 3431–3437, 2013.